2007
DOI: 10.1101/gad.439007
|View full text |Cite
|
Sign up to set email alerts
|

ASY1 mediates AtDMC1-dependent interhomolog recombination during meiosis in Arabidopsis

Abstract: ASY1 is an Arabidopsis protein required for synapsis and crossover formation during meiosis. The chronology of meiotic recombination has been investigated in wild type and an asy1 mutant. We observe a delay between the appearance of chromatin-associated AtSPO11-1 foci and DNA double-strand break (DSB) formation, which occurs contemporaneously with chromosome axis formation and transition of ASY1 from chromatin-associated foci to a linear axis-associated signal. DSBs are formed independently of ASY1 in an AtSPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
326
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(366 citation statements)
references
References 69 publications
(84 reference statements)
33
326
1
Order By: Relevance
“…2 and SI Appendix, Fig. S9) and roughly coincident with the recombination hot spots reported recently (15). Sanger sequencing of PCR products, from unique pairs of primers in the Arabidopsis genome, confirmed that 17 putatively shared loci sampled (eight gene conversions or nine small COs) were indeed shared among different plants.…”
Section: Recombination Events Are In Domains Of High Diversity and Lomentioning
confidence: 70%
“…2 and SI Appendix, Fig. S9) and roughly coincident with the recombination hot spots reported recently (15). Sanger sequencing of PCR products, from unique pairs of primers in the Arabidopsis genome, confirmed that 17 putatively shared loci sampled (eight gene conversions or nine small COs) were indeed shared among different plants.…”
Section: Recombination Events Are In Domains Of High Diversity and Lomentioning
confidence: 70%
“…This result is surprising because each GC should originate from a SPO11-mediated DSB, regardless of whether the GC is associated with a CO or a NCO. Although DSBs have not been directly measured in Arabidopsis, several groups have used immunolocalization of recombination proteins such as RAD51 and DMC1 to provide indirect estimates of DSBs ranging from 120 to 220 per meiosis (39)(40)(41). Even if every DSB resulted in a GC, the reported levels appear to be much too high.…”
Section: Resultsmentioning
confidence: 97%
“…We detected only ;15 (nine COs + six NCOs) recombination events per meiosis; however, fluorescence immunolocalization studies in Arabidopsis detected about 120 AtRAD51 foci per meiotic cell (Sanchez-Moran et al 2007), suggesting that there are over 100 DBS sites in a single meiosis. It is possible that there are many recombination events, but most are not detected because the sizes of DSB gaps and GC tracts are very small.…”
Section: The Low Frequency Of Detected Ncos and Possible Short Gc Tractsmentioning
confidence: 99%